Response of vermicompost and nitrogen on growth, yield and quality of bottle gourd [ Lagenaria siceraria (Mol.) Standl.] (Indian Journal of Arid Horticulture, 2017)
In the present investigation, the response of bottle gourd to different levels of vermicompost (control, 3, 6 and 9tones ha- 1) and nitrogen (control, 50, 75 and 100 kg ha-1) was studied at SKRAU, Bikaner during summer season of 2016.The vermicompost applied at the rate of 6 tones ha-1 has shown least number of days for appearance of first female flower,while number of primary branches per vine, length of leaf ( cm), per cent fruit set, fruit length, weight and total yield per vineetc. were found maximum in plants applied with 9 tones ha- 1• The application of increasing levels of nitrogen 100 kg ha- 1hassignificantly increased the length of leaf, per cent fruit set, number of fruits per vine, fruit length, weight and total yield pervine etc., chlorophyll content in plant (mg/100), P uptake by plant and available N content in soil after harvesting comparedto the control. The treatment combination of vermicompost (9 t ha- 1) + nitrogen (100 kg ha- 1) has showed maximum numberof primary branches per vine, leaf length (cm), per cent fruit set, number of fruits per vine etc. compared to the control plants.The maximum yield (q ha- 1) was found under the treatment combination of vermicompost (9 t ha- 1) + nitrogen (100 kg ha- 1)while remaining treatment combinations was at par with each other. The higher nitrogen content as well as B: C ratio (l.70)in plant was observed in the treatment combination of vermicompost (6 t ha- 1) + nitrogen (100 kg ha- 1).
Keywords: Bottle gourd; Vermicompost; Nitrogen; Growth; Yield; Quality